Numerical analysis of a developing turbulent flow and conjugate heat transfer for molten salt and liquid sodium in a solar receiver. (25th November 2022) - Khuda, Mahfuja A; Khalesi, Javad; Tu, Zecan; Long, Yun; Piccioni Koch, Daniela; Sarunac, Nenad
Highlights: Temperature uniformity within a solar receiver using guide vanes was investigated. Friction coefficient and Nu number were reported for liquid sodium and molten salt. The effect of wall heat flux on fluid flow and heat transfer was studied. Abstract: A numerical analysis of the developing flow and conjugate heat transfer in a solar receiver tube with a three-blade guide vane at the tube inlet was performed to investigate the effect of guide vane and working fluid on the flow and temperature distribution in a solar receiver tube subjected to the boundary condition of the non-uniform wall heat flux. Three dimensional Navier-Stokes, energy, and Laplace equations were solved numerically using Fluent code for the molten solar salt and liquid sodium as the working fluids. The SST k-ω turbulence model was used to predict the flow behavior inside the tube. The values of the friction coefficient and Nu number predicted by the numerical analysis were compared to and validated against experimental correlations from the literature. The numerical results show that a significantly lower pressure drop, and more uniform temperature distribution in the receiver tube are achievable by using the liquid sodium, compared to the molten solar salt. Application of a three-blade guide vane improves temperature uniformity across the receiver tube cross-section, but increases pressure drop in the developing flow region and, thus the overall pressure drop in the tube. The increase in the pressure drop is attributed to the swirling flow and higher friction coefficient compared to the fully developed flow for both working fluids studied in this work.